Response of Cylindrical Shells to Lateral Blast Load. Issue 3 (September 2013) - Yuen, Steeve Chung Kim; Nurick, Gerald N.; Brinckmann, Hugh B.; Blakemore, Dylan
This paper presents a series of experimental and numerical results on cylindrical shells subjected to external localised blast loads. The cylindrical shells are laterally loaded in the mid span using varying masses of plastic explosive (PE4) over a prescribed load diameter of 22.5 mm, 30 mm and 45 mm detonated at a stand-off distance of 13 mm. Another series of tests is also carried out at a load diameter of 30 mm and charge mass of 16 g but with varying stand-off distance. The specimen and explosive are mounted on a ballistic pendulum which is used to determine the impulsive load imparted onto the cylindrical shells. The resultant impulses produce failures ranging from large inelastic deformation of the cylindrical shell to tearing of the structure associated with large inelastic deformation. The results are compared with analytical solution developed by Wierzbicki and Hoo Fatt[1] and numerical simulations carried out in ANSYS/AutoDYN v12.1. While the analytical solutions underestimate the permanent midpoint deflection there are good correlations with the numerical simulations.